Effects of Defense Suppliers’ Practice of Online Character Education on the Employees’ Learning Motivation and Perception of Integrity During COVID-19 - Hsiao, Hong-Chin (Frontiers in Psychology, 2021)
The 21st century marks a period where pursuit of innovation, advance of information media, and diverse value has gained great significance. In the face of information, economic impact and challenge, advanced countries particularly emphasize online character education, as cultivating the people’s sound character to have good attitude towards life and that teaching people correct core value and moral thinking to cultivate good character could create personal happiness and social harmony, enhance national competitiveness, and be the key in a more harmonious society in the future. Education is the stable rock of ethics and morality, as the foundation to build a house; unstable rock would result in the danger of collapse. People’s sense of propriety, justice, integrity, and honor, as well as morality is running in the opposite direction nowadays. In such social climate, online character education indeed plays an extremely important role. Taking employers of defense suppliers for Ministry of National Defense, Taiwan, as the empirical subjects, 226 employers are preceded the 20-week (4 hours per week for total 80 hours) experimental teaching research. The research results reveal that 1.online character education would affect learning motivation, 2.online character education would affect perception of integrity, and 3.learning motivation presents significantly positive effects on perception of integrity. According to the results to propose discussions, it is expected to help defense suppliers cultivate good social interaction skills and character to build the harmonious interpersonal relationship.